Purification technology for regenerated DMT in chemical recovery process of waste polyester
By using an adsorption film formed by hydroxylated hexagonal boron nitride and functional anion modified layered bimetallic hydroxide (LDH), the waste polyester alcoholylic solution is adsorbed, which solves the problem of difficult to remove metal ions and dye impurities in the alcoholylic solution in the prior art, improves the purity of the alcoholylic solution, and reduces the energy consumption during the purification process of regenerated DMT.
Patent Information
- Application Number
- CN202510304337.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The prior art is difficult to effectively remove metal ions and dye impurities in the alcoholylation solution during chemical recycling of waste polyesters, resulting in complex purification process and high energy consumption of regenerated DMT.
The adsorption film formed by hydroxylated hexagonal boron nitride and functional anion modified layered bimetallic hydroxide (LDH) is adsorbed to the waste polyester alcoholylic solution to remove impurities.
The purity of the alcohol solution is improved, the difficulty of decompression distillation during the purification process of regenerated DMT is reduced, the number of transesterification cycles is reduced, and energy consumption is reduced.
Abstract
Description
Technical Field
[0001] The invention relates to the field of waste polyester degradation and regeneration, and in particular to a purification technology for regenerated DMT in a waste polyester chemical recovery process. Background Art
[0002] With the progress of social productivity and the development of industrial technology, the application of polyester has spread to all walks of life. Among them, polyethylene terephthalate (PET) is widely used in textiles, automobiles, homes, energy storage, medical and electronic devices due to its excellent chemical and physical properties. It is currently the most widely used polyester material in the world. The wide range of applications has caused a large amount of PET waste to accumulate, and also brought serious environmental pollution and waste of resources. Therefore, the recycling of waste polyester is an urgent problem to be solved.
[0003] The main recycling methods of PET in industrial applications are physical recycling and chemical recycling. Physical recycling refers to the method of separating, crushing, washing and drying waste PET and then granulating it. The mechanical stress and high temperature environment during processing will increase side reactions, causing the viscosity and molecular weight of recycled PET to decrease, affecting the quality of recycled polyester products. Chemical recycling is to depolymerize the PET molecular chain through solvents, convert it into monomers or oligomers, and further purify it to be reused as chemical raw materials, which can achieve a true recycling cycle. Among them, glycol hydrolysis is the most widely used at present. The glycol hydrolysis method has mild reaction conditions and a simple process flow. It can also use the glycol hydrolysis regenerated monomer dihydroxyethylene terephthalate (BHET) to undergo an ester exchange reaction with methanol to prepare recycled dimethyl terephthalate (DMT) comparable to virgin petroleum-based materials. It is currently the most promising process route for the industrial preparation of high-quality recycled polyester materials.
[0004] Since most PET waste materials have complex components and contain a variety of heavy metal ions, dyes and additives, the alcoholysis liquid after alcoholysis and transesterification contains more impurities, which increases the difficulty of separating and purifying the regenerated DMT. The patent with application number CN202410490800.X discloses a continuous chemical recovery process for PET polyester: waste PET products are sent into a depolymerization reactor, depolymerized to form a depolymerization reaction liquid, the depolymerization reaction liquid is centrifuged for the first time to form floccules and depolymerization reaction liquid, the floccules are washed, the residual depolymers are recovered, the washed floccules are centrifuged and filtered for the second time, and the washing liquid and the filter press liquid are used as the reaction liquid for re-reaction; BHET and unreacted EG in the depolymerization reaction liquid are separated, and the unreacted EG is separated in turn by a light removal tower and a heavy removal tower to obtain high-purity EG, and BHET is collected and added to methanol for transesterification reaction to generate DMT; DMT is crystallized, the DMT crystals are broken up, EG is added for washing, the washed DMT crystals are melted into liquid, and the liquid DMT is further separated and purified. The patent with application number CN202011227868.7 discloses a method and equipment for obtaining DMT from distillation still residue: the distillation still residue is evaporated under negative pressure by a thin film evaporator, and DMT is separated by gas phase condensation; the recycled liquid is the waste polyester raw material, alcoholysis agent and alcoholysis catalyst being continuously alcoholyzed in a molten state, ester exchange synthesizing ester exchange products, DMT crystallization of the ester exchange products, and washing the DMT crystals with methanol to obtain a DMT filter cake; the DMT filter cake is purified by a short-process distillation system at 6.65 Kpa and 200 ° C to obtain pure DMT and distillation still residue. The above patent is aimed at a simple system in which ethylene glycol exists, which can purify DMT to a certain extent. However, since the alcoholysis solution of PET is relatively complex and generally contains impurities such as metals, dyes and organic pollutants, it is difficult to completely remove all impurities in the alcoholysis solution by simple vacuum distillation and other methods. Therefore, it is necessary to increase the pretreatment technology for the purification of the alcoholysis solution, reduce the energy consumption in the purification process of the regenerated DMT, and effectively reduce the number of ester exchange cycles. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a purification technology for regenerated DMT in the process of chemical recovery of waste polyester. The purification technology provided by the present application can make the waste polyester alcoholysis liquid have higher purity, and can effectively reduce the difficulty of subsequent vacuum distillation purification of regenerated DMT.
[0006] In view of this, the present application provides a purification technology for regenerating DMT in a waste polyester chemical recovery process, comprising the following steps:
[0007] S1) mixing a divalent metal salt, a trivalent metal salt, an alkaline reagent and water, and vacuum drying the product after the reaction to obtain a layered double hydroxide precursor;
[0008] S2) mixing the precursor and a solution containing functional anions, and vacuum drying the product obtained after intercalation modification to obtain a layered double metal hydroxide modified with functional anions;
[0009] S3) electrostatically self-assembling hydroxylated hexagonal boron nitride and layered double metal hydroxide, filtering the obtained mixed solution on a carrier, and drying to obtain an adsorption film;
[0010] S4) The waste polyester alcoholysis liquid is adsorbed by the adsorption membrane.
[0011] Preferably, in step S1), the metal cations in the divalent metal salt include Fe 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ and Mg 2+ One or more of the trivalent metal salts, wherein the metal cations include Ni 3+ , Fe 3+ 、Al 3+ and Ti 3+ One or more of; the anions of the divalent metal salt and the trivalent metal salt are independently selected from SO4 2- 、NO3 - 、CO3 2- and Cl - The alkaline reagent comprises one of urea, ammonia water and sodium hydroxide.
[0012] Preferably, in step S1), the mass ratio of the divalent metal salt to the trivalent metal salt is (0.5-5):1, and the ratio of the total mass of the divalent metal salt and the trivalent metal salt to the mass of the alkaline reagent is 1:(0.5-5); the reaction temperature is 50-100°C, and the reaction time is 5-25h.
[0013] Preferably, in step S2), the functional anions of the solution containing functional anions include (MoS4) 2- 、MoO4 2- , VO4 - , BO3 3- 、BF4 - 、P4O3 - One or more of the following: the intercalation modification time is 5 to 36 hours; the vacuum drying temperature is 50 to 100° C., and the time is 5 to 10 hours.
[0014] Preferably, in step S3), the preparation method of the hydroxylated hexagonal boron nitride is specifically as follows:
[0015] The hexagonal boron nitride and alkali solution are mixed and ball-milled for hydroxylation modification to obtain hydroxylated hexagonal boron nitride.
[0016] Preferably, the alkali solution includes one or more of NaOH, Ca(OH)2, KOH and LiOH, and the mass ratio of the hexagonal boron nitride to the alkali solution is 1:(0.1-10).
[0017] Preferably, the ball milling time is 2 to 15 hours, the speed of the ball mill is 200 to 500 rpm, and the forward and reverse rotation interval of the ball mill is 30 to 100 seconds.
[0018] Preferably, in step S3), the mass ratio of the hydroxylated hexagonal boron nitride to the layered double hydroxide is 1:(0.1-25), the drying temperature is 20-100° C., and the drying time is 1-5 h.
[0019] Preferably, in step S3), before the electrostatic self-assembly, the process comprises: subjecting the hydroxylated hexagonal boron nitride and the layered double metal hydroxide to ultrasonic vibration respectively, and the time of the ultrasonic vibration is 0.5-6 hours.
[0020] The present application also provides a method for preparing an adsorption film, comprising the following steps:
[0021] S1) mixing a divalent metal salt, a trivalent metal salt, an alkaline reagent and water, and vacuum drying the product after the reaction to obtain a layered double hydroxide precursor;
[0022] S2) mixing the precursor with a solution containing functional anions, and vacuum drying the product obtained after intercalation modification to obtain a layered double metal hydroxide modified with functional anions;
[0023] S3) The hydroxylated hexagonal boron nitride and the layered double hydroxide are subjected to electrostatic self-assembly, and the obtained mixed solution is filtered on the carrier and dried to obtain an adsorption film.
[0024] The present application provides a purification technology for regenerating DMT in a waste polyester chemical recovery process, which firstly mixes a divalent salt, a trivalent metal salt, an alkaline reagent and water, vacuum dries the reaction product to obtain a layered double metal hydroxide precursor, then mixes the precursor with a solution containing functional anions, vacuum dries the product obtained after intercalation modification to obtain a layered double metal hydroxide modified with functional anions, then electrostatically self-assembles hydroxylated hexagonal boron nitride and the layered double metal hydroxide, and filters the obtained mixed solution on a carrier, and obtains an adsorption film after drying; finally, the polyester alcoholysis solution is adsorbed through the adsorption film, so as to obtain an alcoholysis solution with high purity; in the waste polyester chemical recovery process, In the purification technology of regenerated DMT, the present application uses an adsorption film formed by hydroxylated hexagonal boron nitride and functional anion-modified layered double hydroxide (LDH) to adsorb waste polyester alcoholysis liquid, wherein the hydrophilicity and high specific surface area of hydroxylated hexagonal boron nitride give it good adsorption performance, and the functional anion-modified LDH has a special layered structure and a high specific surface area, which is more conducive to the adsorption of impurities such as heavy metal ions and organic dyes. Therefore, the above-mentioned adsorption film can efficiently adsorb metal ions and dyes in the alcoholysis liquid, so that the purified alcoholysis liquid has a higher purity, which effectively reduces the difficulty of subsequent vacuum distillation purification in the process of regenerating DMT from the waste polyester alcoholysis liquid. DETAILED DESCRIPTION
[0025] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0026] In view of the difficulty in purifying waste polyester alcoholysis liquid in the prior art, especially the problem of metal ion and dye adsorption and removal, the present application provides a preparation method of a layered double hydroxide (LDH-BN) adsorption membrane modified with hydroxylated hexagonal boron nitride and functional anions and a purification technology for regenerating DMT in the chemical recovery process of waste polyester, which can effectively improve the purity of the waste polyester alcoholysis liquid by adsorbing metal ions and dyes in the waste polyester alcoholysis liquid. Specifically, the embodiment of the present invention discloses a preparation method of an adsorption membrane, comprising the following steps:
[0027] S1) mixing a divalent metal salt, a trivalent metal salt, an alkaline reagent and water, and vacuum drying the product after the reaction to obtain a layered double hydroxide precursor;
[0028] S2) mixing the precursor with a solution containing functional anions, and vacuum drying the product obtained after intercalation modification to obtain a layered double metal hydroxide modified with functional anions;
[0029] S3) The hydroxylated hexagonal boron nitride and the layered double hydroxide are subjected to electrostatic self-assembly, and the obtained mixed solution is filtered on the carrier and dried to obtain an adsorption film.
[0030] In the process of preparing the adsorption film, the present invention first mixes a divalent metal salt, a trivalent metal salt, an alkaline reagent and water, and vacuum dries the product after the reaction to obtain a layered double hydroxide precursor; in this process, the metal cations in the divalent metal salt include Fe 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ and Mg 2+ Specifically, the metal cation in the divalent metal salt is selected from Fe 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ and Mg 2+ More specifically, the metal cation in the divalent metal salt is selected from Mg 2+ and Fe 2+ Combination of Cu 2+ and Zn 2+ Combination of Mg 2+ and Cu 2+ Combination or Ni 2+ and Cu 2+ The metal cation in the trivalent metal salt includes Ni 3+ , Fe 3+ 、Al 3+ and Ti 3+ Specifically, the metal salt ion in the trivalent metal salt is selected from Ni 3+ , Fe 3+ 、Al 3+ and Ti 3+ The anions of the divalent metal salt and the trivalent metal salt are independently selected from SO4 2- 、NO3 - 、CO3 2- and Cl - Specifically, the anions of the divalent metal salt and the trivalent metal salt are independently selected from SO4 2- 、NO3 - and Cl -One or two of the above. The alkaline agent includes one of urea, ammonia water and sodium hydroxide. Specifically, the alkaline agent is selected from urea or sodium hydroxide. The mass ratio of the divalent metal salt to the trivalent metal salt is (0.5~5):1. Specifically, the mass ratio of the divalent metal salt to the trivalent metal salt is (0.7~3):1. More specifically, the mass ratio of the divalent metal salt to the trivalent metal salt is 1:1, 1.5:1 or 2:1. The ratio of the total mass of the divalent metal salt and the trivalent metal salt to the mass of the alkaline agent is 1:(0.5~5). Specifically, the ratio of the total mass of the divalent metal salt and the trivalent metal salt to the mass of the alkaline agent is 1:(0.8~3). More specifically, the ratio of the total mass of the divalent metal salt and the trivalent metal salt to the mass of the alkaline agent is 1:1, 1:1.3 or 1:1.7. The reaction temperature is 50-100°C and the reaction time is 5-25h; specifically, the reaction temperature is 60-97°C and the reaction time is 10-24h. The vacuum drying temperature is 50-100°C and the reaction time is 5-10h. More specifically, the vacuum drying temperature is 60-80°C and the reaction time is 6-8h. The preparation of the layered double hydroxide precursor is more specifically as follows:
[0031] A divalent metal salt, a trivalent metal salt and an alkaline reagent are dissolved in deionized water in a certain proportion, and the mixture is heated and stirred at a fixed reflux temperature and time. After the reaction is completed, the product is filtered, washed with deionized water and anhydrous ethanol several times, and finally vacuum dried at a fixed temperature for a period of time to obtain a layered double hydroxide (LDH) precursor.
[0032] The present application then mixes the precursor and a solution containing functional anions, and vacuum dries the product obtained after intercalation modification to obtain a layered double metal hydroxide modified with functional anions (modified LDH); in this process, the functional anions of the solution containing functional anions include (MoS4) 2- 、MoO4 2- , VO4 - , BO3 3- 、BF4 - and P4O3 - One or more of, specifically, the functional anion is selected from (MoS4) 2- 、MoO4 2- , VO4 - , BO3 3- 、BF4 - and P4O3 - More specifically, the functional anion is selected from (MoS4) 2- 、MoO4 2- , VO4 - or P4O3- ; The intercalation modification time is 5 to 36 hours, specifically, the intercalation modification time is 8 to 24 hours. The vacuum drying temperature is 50 to 100°C, and the time is 5 to 10 hours, specifically, the vacuum drying temperature is 60 to 80°C, and the time is 6 to 8 hours. The layered double hydroxide is more conducive to the adsorption of heavy metal ions and dyes after functional anion modification. The preparation process of the modified LDH is specifically as follows:
[0033] The precursor is added to a solution containing functional anions, and intercalation modification is carried out at room temperature. After the reaction is completed, the product is filtered, washed several times with deionized water and anhydrous ethanol, and finally vacuum dried at a fixed temperature for a period of time to obtain a layered double metal hydroxide modified with functional anions.
[0034] According to the present invention, the hydroxylated hexagonal boron nitride and the modified LDH are then subjected to electrostatic self-assembly, the obtained mixed solution is filtered on a carrier, and an adsorption film is obtained after drying; in this process, the preparation method of the hydroxylated hexagonal boron nitride is specifically as follows:
[0035] The hexagonal boron nitride and alkali solution are mixed and ball-milled for hydroxylation modification to obtain hydroxylated hexagonal boron nitride.
[0036] In the preparation process of hydroxylated hexagonal boron nitride, the alkali solution includes one or more of NaOH, Ca(OH)2, KOH and LiOH, and specifically, the alkali solution is selected from one of NaOH, Ca(OH)2, KOH and LiOH. The mass ratio of hexagonal boron nitride to alkali solution is 1: (0.1-10), specifically, the mass ratio of hexagonal boron nitride to alkali solution is 1: (0.5-3.75), more specifically, the mass ratio of hexagonal boron nitride to alkali solution is 1: (0.75-3), more specifically, the mass ratio of hexagonal boron nitride to alkali solution is 1: (1.5-2.5). The ball milling time is 2-15h, the speed of the ball mill is 200-500rmp, and the forward and reverse interval of the ball mill is 30-100s; specifically, the ball milling time is 4-8h, the speed of the ball mill is 300-400rmp, and the forward and reverse interval is 40-60s. The hexagonal boron nitride is modified by the hydroxylation, thereby enhancing the hydrophilicity of the hexagonal boron nitride.
[0037] In the above steps, the mass ratio of the hydroxylated hexagonal boron nitride to the layered double metal hydroxide is 1: (0.1~25), specifically, the mass ratio of the hydroxylated hexagonal boron nitride to the layered double metal hydroxide is 1: (0.5~5), more specifically, the mass ratio of the hydroxylated hexagonal boron nitride to the layered double metal hydroxide is 1: (2~2.5). The drying temperature is 20~100°C, and the time is 1~5h. Specifically, the drying temperature is 50~60°C, and the time is 1~3h. The preparation process of the adsorption film is specifically as follows:
[0038] Hydroxylated h-BN and modified LDH are respectively prepared into suspensions by ultrasonic oscillation, and the two suspensions are mixed together for electrostatic self-assembly. After the mixed liquid is settled, it is filtered on a ceramic membrane carrier, and the filtered product is dried at a fixed temperature and time to obtain a uniform LDH-BN adsorption film.
[0039] Furthermore, the present application also provides a method for purifying waste polyester alcoholysis solution using the above-mentioned LDH-BN adsorption membrane, that is, the present application provides a purification technology for regenerating DMT in the waste polyester chemical recovery process, comprising the following steps:
[0040] S1) mixing a divalent metal salt, a trivalent metal salt, an alkaline reagent and water, and vacuum drying the product after the reaction to obtain a layered double hydroxide precursor;
[0041] S2) mixing the precursor and a solution containing functional anions, and vacuum drying the product obtained after intercalation modification to obtain a layered double metal hydroxide modified with functional anions;
[0042] S3) electrostatically self-assembling hydroxylated hexagonal boron nitride and layered double metal hydroxide, filtering the obtained mixed solution on a carrier, and drying to obtain an adsorption film;
[0043] S4) The polyester alcoholysis liquid is adsorbed by the adsorption membrane.
[0044] In the above purification technology, step S1) to step S3) are the process of preparing the adsorption film, which has been described in detail above and will not be repeated here.
[0045] Finally, the present application adsorbs the waste polyester alcoholysis liquid through the adsorption membrane to achieve the adsorption and removal of metal ions and dye cations in the waste polyester alcoholysis liquid. The waste polyester alcoholysis liquid is specifically the alcoholysis reaction of waste polyester, ethylene glycol and catalyst potassium carbonate, wherein the waste polyester is one or more of waste polyester fiber, waste polyester plastic and waste polyester film; the alcoholysis reaction is an alcoholysis process well known to those skilled in the art, and will not be described here. More specifically, the adsorption membrane is installed on the pipeline equipment, and the alcoholysis liquid is filtered through the LDH-BN adsorption membrane.
[0046] Hexagonal boron nitride is a hexagonal mesh structure crystal composed of nitrogen atoms and boron atoms. The difference in electronegativity between nitrogen atoms and boron atoms causes a charge offset. The unique polarity of the boron-nitrogen bond and the high specific surface area of hexagonal boron nitride make it have good adsorption capacity for metal ions and dyes. Layered double hydroxide (LDH) is composed of positively charged metal hydroxide layers and negatively charged interlayer anions. It has a special layered structure and a high specific surface area, and has good adsorption performance for impurities such as heavy metal ions and organic dyes in waste liquid. LDH modified by anions and h-BN modified by hydroxylation can be composited by simple electrostatic self-assembly to form a stable adsorption filtration membrane, which overcomes the shortcomings of current membrane adsorption materials such as low permeability flux, insufficient adsorption efficiency, and poor stability, and further improves the adsorption capacity of the two. It is used for the pretreatment of waste polyester alcoholysis liquid, which effectively reduces the difficulty of subsequent vacuum distillation purification of regenerated DMT, and at the same time makes the purified alcoholysis liquid have a higher purity.
[0047] In order to further understand the present invention, the purification technology of regenerated DMT in the chemical recovery process of waste polyester provided by the present invention is described in detail below in conjunction with the embodiments, and the protection scope of the present invention is not limited by the following embodiments.
[0048] Example 1
[0049] (1) 0.8 g of hexagonal boron nitride (h-BN) and 0.6 g of NaOH were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN to obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 5 h, ball-mill speed of 400 rmp, and forward and reverse rotation interval of 30 s.
[0050] (2) MgCl2, FeCl2, AlCl3 and urea were dissolved in 600 mL of deionized water in a mass ratio of 1:2:1:4, and then the mixture was heated at reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried in vacuum at 60 °C for 6 h to obtain Mg-Fe-Al LDH precursor;
[0051] (3) Add the precursor in (2) to 500 mL of (MoS4) 2- After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 6 h to obtain (MoS4) 2- Modified Mg-Fe-Al LDH;
[0052] (4) Hydroxylation of h-BN and (MoS4) 2- The modified Mg-Fe-Al LDH was ultrasonically vibrated for 4 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 1:1 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 50 °C for 1 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 1:1.
[0053] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0054] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 96.5%, the removal rate of cationic red GTL was 93.2%, the removal rate of cationic yellow X-6G was 90.6%, and the removal rate of brilliant red 5GN was 94.5%. The results are shown in Table 1.
[0055] Example 2
[0056] (1) 1.0 g h-BN and 0.5 g NaOH were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN and obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 4 h, ball-mill speed of 400 rpm, and forward and reverse rotation interval of 30 s.
[0057] (2) MgCl2, FeSO4, AlCl3 and urea were dissolved in 600 mL of deionized water at a mass ratio of 1:1:1:4, and then the mixture was heated at reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol three times, and finally vacuum dried at 60 °C for 6 h to obtain Mg-Fe-Al LDH precursor;
[0058] (3) Add the precursor described in (2) to 500 mL of (MoS4) 2-After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 6 h to obtain (MoS4) 2- Modified Mg-Fe-Al LDH;
[0059] (4) Hydroxylation of h-BN and (MoS4) 2- The modified Mg-Fe-Al LDH was ultrasonically vibrated for 3 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 1:1 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 50 °C for 1 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 1:1.
[0060] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0061] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 87.4%, the removal rate of cationic red GTL was 79.8%, the removal rate of cationic yellow X-6G was 81.3%, and the removal rate of brilliant red 5GN was 80.1%. The specific results are shown in Table 1.
[0062] Example 3
[0063] (1) 1.0 g h-BN and 0.5 g Ca(OH)2 were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN to obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 5 h, ball-mill speed of 400 rpm, and forward and reverse rotation interval of 30 s.
[0064] (2) MgCl2, Fe(NO3)2, AlCl3 and sodium hydroxide were dissolved in 600 mL of deionized water in a mass ratio of 1:2:1:4, and then the mixture was heated at reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol three times, and finally dried in vacuum at 60 °C for 6 h to obtain Mg-Fe-Al LDH precursor;
[0065] (3) Add the precursor described in (2) to 500 mL of MoO4 2- The intercalation modification was carried out at room temperature. After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol three times, and finally dried in vacuum at 60 °C for 6 h to obtain MoO4 2− Modified Mg-Fe-Al LDH;
[0066] (4) Hydroxylation of h-BN and MoO4 2- The modified Mg-Fe-Al LDH was ultrasonically vibrated for 3 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 1:1 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 50 °C for 1 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 1:1.
[0067] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0068] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 87.8%, the removal rate of cationic red GTL was 81.2%, the removal rate of cationic yellow X-6G was 82.5%, and the removal rate of brilliant red 5GN was 81.2%. The specific results are shown in Table 1.
[0069] Example 4
[0070] (1) 0.5 g h-BN and 1.0 g KOH were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN to obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 5 h, ball-mill speed of 400 rpm, and forward and reverse rotation interval of 60 s.
[0071] (2) ZnCl2, CuCl2, FeCl3 and sodium hydroxide were dissolved in 600 mL of deionized water in a mass ratio of 1:2:1:4, and then the mixture was heated at reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally vacuum dried at 60 °C for 6 h to obtain Zn-Cu-Fe LDH precursor;
[0072] (3) Add the precursor described in (2) to 400 mL of BO3 3- After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 6 h to obtain BO3 3- Modified Zn-Cu-Fe LDH;
[0073] (4) Hydroxylation of h-BN and BO3 3-The modified Zn-Cu-Fe LDH was ultrasonically vibrated for 3 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 1:2 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 50 °C for 1 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 1:2.
[0074] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0075] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 75.4%, the removal rate of cationic red GTL was 78.8%, the removal rate of cationic yellow X-6G was 82.3%, and the removal rate of brilliant red 5GN was 77.3%. The specific results are shown in Table 1.
[0076] Example 5
[0077] (1) 0.8 g h-BN and 2.0 g LiOH were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN to obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 8 h, ball-mill speed of 500 rpm, and forward and reverse rotation interval of 40 s.
[0078] (2) ZnCl2, Cu(NO 3)2 , FeCl3 and sodium hydroxide were dissolved in 600 mL of deionized water in a mass ratio of 1:2:1:4, and then the mixture was heated at a reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried in vacuum at 60 °C for 6 h to obtain a Zn-Cu-Fe LDH precursor;
[0079] (3) Add the precursor described in (2) to 400 mL of BO3 3- After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 6 h to obtain BO3 3- Modified Zn-Cu-Fe LDH;
[0080] (4) Hydroxylation of h-BN and BO3 3-The modified Zn-Cu-Fe LDH was ultrasonically vibrated for 3 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 2:1 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 50 °C for 1 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 2:1.
[0081] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0082] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 75.4%, the removal rate of cationic red GTL was 73.2%, the removal rate of cationic yellow X-6G was 72.3%, and the removal rate of brilliant red 5GN was 67.8%. The specific results are shown in Table 1.
[0083] Example 6
[0084] (1) 0.8 g h-BN and 3.0 g LiOH were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN to obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 8 h, ball-mill speed of 500 rpm, and forward and reverse rotation interval of 30 s.
[0085] (2) ZnCl2, Cu(NO 3)2 , FeCl3 and sodium hydroxide were dissolved in 600 mL of deionized water in a mass ratio of 1:2:3:5, and then the mixture was heated at a reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried in vacuum at 60 °C for 6 h to obtain a Zn-Cu-Fe LDH precursor;
[0086] (3) Add the precursor described in (2) to 400 mL of P4O3 - After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 6 h to obtain P4O3 - Modified Zn-Cu-Fe LDH;
[0087] (4) Hydroxylation of h-BN and P4O3 -The modified Zn-Cu-Fe LDH was ultrasonically vibrated for 3 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 2:1 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 50 °C for 1 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 2:1.
[0088] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0089] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 82.4%, the removal rate of cationic red GTL was 83.6%, the removal rate of cationic yellow X-6G was 79.9%, and the removal rate of brilliant red 5GN was 77.8%, as shown in Table 1.
[0090] Example 7
[0091] (1) 1.0 g h-BN and 3.0 g LiOH were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN to obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 6 h, ball-mill speed of 450 rpm, and forward and reverse rotation interval of 30 s.
[0092] (2) MgCl2, Cu(NO 3)2 , FeCl3 and sodium hydroxide were dissolved in 600 mL of deionized water in a mass ratio of 1:2:3:5, and then the mixture was heated at a reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 6 h to obtain a Mg-Cu-Fe LDH precursor;
[0093] (3) Add the precursor described in (2) to 400 mL of P4O3 - After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 5 h to obtain P4O3 - Modified Mg-Cu-Fe LDH;
[0094] (4) Hydroxylation of h-BN and P4O3 -The modified Mg-Cu-Fe LDH was ultrasonically vibrated for 3 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 2:1 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 50 °C for 1 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 2:1.
[0095] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0096] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 82.4%, the removal rate of cationic red GTL was 77.6%, the removal rate of cationic yellow X-6G was 78.9%, and the removal rate of brilliant red 5GN was 75.4%, as shown in Table 1.
[0097] Example 8
[0098] (1) 2.0 g h-BN and 3.0 g NaOH were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN to obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 6 h, ball-mill speed of 500 rpm, and forward and reverse rotation interval of 30 s.
[0099] (2) NiCl2, Cu(NO 3)2 , FeCl3 and sodium hydroxide were dissolved in 500 mL of deionized water in a mass ratio of 1:1:3:5, and then the mixture was heated at a reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol for 4 times, and finally dried in vacuum at 60 °C for 6 h to obtain a Ni-Cu-Fe LDH precursor;
[0100] (3) Add the precursor described in (2) to 400 mL of P4O3 - After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 5 h to obtain P4O3 - Modified Ni-Cu-Fe LDH;
[0101] (4) Hydroxylation of h-BN and P4O3 -The modified Ni-Cu-Fe LDH was ultrasonically vibrated for 3 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 2:5 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 50 °C for 1 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 2:5.
[0102] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0103] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 68.5%, the removal rate of cationic red GTL was 76.1%, the removal rate of cationic yellow X-6G was 78.6%, and the removal rate of brilliant red 5GN was 75.7%, as shown in Table 1.
[0104] Example 9
[0105] (1) 2.0 g h-BN and 1.0 g NaOH were mixed and milled in a planetary ball mill. The milling conditions were as follows: milling time of 6 h, mill speed of 400 rpm, and forward and reverse rotation interval of 30 s to hydroxylate h-BN.
[0106] (2) NiCl2, Cu(NO 3)2 , TiCl3 and sodium hydroxide were dissolved in 500 mL of deionized water in a mass ratio of 1:1:1:5, and then the mixture was heated at a reflux temperature of 97 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol for 4 times, and finally dried in vacuum at 60 °C for 6 h to obtain a Ni-Cu-Ti LDH precursor;
[0107] (3) Add the precursor described in (2) to 400 mL of VO4 - After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 5 h to obtain VO4 - Modified Ni-Cu-Ti LDH;
[0108] (4) Hydroxylation of h-BN and VO4 -The modified Ni-Cu-Ti LDH was ultrasonically vibrated for 3 h to prepare suspensions, and the two suspensions were mixed together in a ratio of 1:5 to allow electrostatic self-assembly. After the mixed solution was settled, it was filtered on a ceramic membrane carrier, and the filtered product was dried at 60 °C for 3 h to obtain a uniform LDH-BN adsorption membrane with a mass ratio of 1:5.
[0109] (5) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH-BN adsorption membrane to purify the alcoholysis solution.
[0110] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion, the changes before and after of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 64.8%, the removal rate of cationic red GTL was 73.7%, the removal rate of cationic yellow X-6G was 71.0%, and the removal rate of brilliant red 5GN was 76.2%, as shown in Table 1.
[0111] Comparative Example 1
[0112] (1) 0.8 g h-BN and 0.6 g NaOH were mixed and ball-milled in a planetary ball mill to hydroxylate h-BN to obtain hydroxylated h-BN. The ball-milling conditions were as follows: ball-milling time of 5 h, ball-mill speed of 400 rpm, and forward and reverse rotation interval of 30 s.
[0113] (2) The hydroxylated h-BN was ultrasonically vibrated for 4 h to prepare a suspension. After the suspension settled, it was filtered on a ceramic membrane carrier. The filtered product was dried at 50 °C for 1 h to obtain a BN adsorption membrane.
[0114] (3) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the BN adsorption membrane to purify the alcoholysis solution.
[0115] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 46.8%, the removal rate of cationic red GTL was 63.7%, the removal rate of cationic yellow X-6G was 60.1%, and the removal rate of brilliant red 5GN was 51.8%, as shown in Table 1.
[0116] Comparative Example 2
[0117] (1) MgCl2, FeCl2, AlCl3 and urea were dissolved in 600 mL of deionized water at a mass ratio of 1:2:1:4, and then the mixture was heated at reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol three times, and finally dried in vacuum at 60 °C for 6 h to obtain Mg-Fe-Al LDH precursor;
[0118] (2) Add the precursor described in (2) to 500 mL of (MoS4) 2- After the reaction, the product was filtered, washed with deionized water and anhydrous ethanol for 3 times, and finally dried under vacuum at 60 °C for 6 h to obtain (MoS4) 2- Modified Mg-Fe-Al LDH;
[0119] (3) (MoS4) 2- The modified Mg-Fe-Al LDH was ultrasonically vibrated for 4 h to prepare a suspension, and after the suspension settled, it was filtered on a ceramic membrane carrier. The filtered product was dried at 50 °C for 1 h to obtain a uniform LDH adsorption membrane.
[0120] (4) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH adsorption membrane to purify the alcoholysis solution.
[0121] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 58.5%, the removal rate of cationic red GTL was 51.2%, the removal rate of cationic yellow X-6G was 50.3%, and the removal rate of brilliant red 5GN was 49.0%, as shown in Table 1.
[0122] Comparative Example 3
[0123] (1) MgCl2, FeCl2, AlCl3 and urea were dissolved in 600 mL of deionized water at a mass ratio of 1:2:1:4, and then the mixture was heated at reflux temperature of 96 °C and stirred continuously for 24 h. The obtained product was filtered, washed with deionized water and anhydrous ethanol three times, and finally dried in vacuum at 60 °C for 6 h to obtain Mg-Fe-Al LDH precursor;
[0124] (2) Mg-Fe-Al LDH was ultrasonically vibrated for 4 h to prepare a suspension. After the suspension settled, it was filtered on a ceramic membrane carrier. The filtered product was dried at 50 °C for 1 h to obtain a uniform LDH adsorption membrane.
[0125] (3) The above-mentioned adsorption membrane is installed on the pipeline equipment, and the alcoholysis solution is filtered through the LDH adsorption membrane to purify the alcoholysis solution.
[0126] Comparison of Sb in alcoholysis solution before purification 3+ A metal ion and the changes of three commonly used cationic dyes for fiber dyeing: Cationic Red GTL, Cationic Yellow X-6G, and Brilliant Red 5GN: Sb 3+ The removal rate was 35.5%, the removal rate of cationic red GTL was 45.2%, the removal rate of cationic yellow X-6G was 42.3%, and the removal rate of brilliant red 5GN was 43.5%, as shown in Table 1.
[0127] Table 1 Data table of metal ion and cationic dye removal rates in alcoholysis solutions of examples and comparative examples Group <![CDATA[Sb 3+ ]]> Cationic Red GTL Cationic Yellow X-6G Brilliant Red 5GN Example 1 96.5% 93.2% 90.6% 94.5% Example 2 87.4% 79.8% 81.3% 80.1% Example 3 87.8% 81.2% 82.5% 81.2% Example 4 75.4% 78.8% 82.3% 77.3% Example 5 75.4% 73.2% 72.3% 67.8% Example 6 82.4% 83.6% 79.9% 77.8% Example 7 82.4% 77.6% 78.9% 75.4% Example 8 68.5% 76.1% 78.6% 75.7% Example 9 64.8% 73.7% 71.0% 76.2% Comparative Example 1 46.8% 63.7% 60.1% 51.8% Comparative Example 2 58.5% 51.2% 50.3% 49.0% Comparative Example 3 35.5% 45.2% 42.3% 43.5% The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0128] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A purification technology for regenerating DMT in a waste polyester chemical recovery process, comprising the following steps: S1) mixing a divalent metal salt, a trivalent metal salt, an alkaline reagent and water, and vacuum drying the product after the reaction to obtain a layered double hydroxide precursor; S2) mixing the precursor and a solution containing functional anions, and vacuum drying the product obtained after intercalation modification to obtain a layered double metal hydroxide modified with functional anions; S3) electrostatically self-assembling hydroxylated hexagonal boron nitride and layered double metal hydroxide, filtering the obtained mixed solution on a carrier, and drying to obtain an adsorption film; S4) The waste polyester alcoholysis liquid is adsorbed by the adsorption membrane.
2. The purification technology according to claim 1, characterized in that: In step S1), the metal cations in the divalent metal salt include Fe 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ and Mg 2+ One or more of the trivalent metal salts, wherein the metal cations include Ni 3+ , Fe 3+ 、Al 3+ and Ti 3+ One or more of; the anions of the divalent metal salt and the trivalent metal salt are independently selected from SO4 2- 、NO3 - 、CO3 2- and Cl - The alkaline reagent comprises one of urea, ammonia water and sodium hydroxide.
3. The purification technology according to claim 1 or 2, characterized in that: In step S1), the mass ratio of the divalent metal salt to the trivalent metal salt is (0.5-5):1, and the ratio of the total mass of the divalent metal salt and the trivalent metal salt to the mass of the alkaline reagent is 1:(0.5-5); the reaction temperature is 50-100°C, and the reaction time is 5-25h.
4. The purification technology according to claim 3, characterized in that: In step S2), the functional anions of the solution containing functional anions include (MoS4) 2- 、MoO4 2- , VO4 - , BO3 3- 、BF4 - 、P4O3 - One or more of the following: the intercalation modification time is 5 to 36 hours; the vacuum drying temperature is 50 to 100° C., and the time is 5 to 10 hours.
5. The purification technology according to claim 4, characterized in that: In step S3), the preparation method of the hydroxylated hexagonal boron nitride is specifically as follows: The hexagonal boron nitride and alkali solution are mixed and ball-milled for hydroxylation modification to obtain hydroxylated hexagonal boron nitride.
6. The purification technology according to claim 5, characterized in that: The alkali solution includes one or more of NaOH, Ca(OH)2, KOH and LiOH, and the mass ratio of the hexagonal boron nitride to the alkali solution is 1:(0.1-10).
7. The purification technology according to claim 5, characterized in that: The ball milling time is 2-15 hours, the rotation speed of the ball mill is 200-500 rpm, and the forward and reverse rotation interval of the ball mill is 30-100 seconds.
8. The purification technology according to claim 5, characterized in that: In step S3), the mass ratio of the hydroxylated hexagonal boron nitride to the layered double hydroxide is 1:(0.1-25), the drying temperature is 20-100° C., and the drying time is 1-5 hours.
9. The purification technology according to claim 5, characterized in that: In step S3), before the electrostatic self-assembly, the process includes: subjecting the hydroxylated hexagonal boron nitride and the layered double metal hydroxide to ultrasonic vibration respectively, and the time of the ultrasonic vibration is 0.5-6 hours.
10. A method for preparing an adsorption film, comprising the following steps: S1) mixing a divalent metal salt, a trivalent metal salt, an alkaline reagent and water, and vacuum drying the product after the reaction to obtain a layered double hydroxide precursor; S2) mixing the precursor with a solution containing functional anions, and vacuum drying the product obtained after intercalation modification to obtain a layered double metal hydroxide modified with functional anions; S3) The hydroxylated hexagonal boron nitride and the layered double hydroxide are subjected to electrostatic self-assembly, and the obtained mixed solution is filtered on the carrier and dried to obtain an adsorption film.
Citation Information
Patent Citations
Method and equipment for obtaining DMT from rectification kettle residues
CN112354202A
Continuous chemical recovery process for PET (Polyethylene Terephthalate) polyester
CN118546059A
Hydrotalcite precursor adsorbent and preparation method thereof
CN103127900A
Clean production process for treating polyester wastewater through renewable targeted adsorption
CN107244705A
Hydroxylated boron nitride composite film, and preparation method and application thereof
CN112023702A
Cited By
Preparation method of regenerated low-melting-point polyester
CN121159827A
A method for the preparation of a recycled low-melting polyester
CN121159827B